Factor the following: 1) 9 - rReturn to the tutorial^{2}From the form (a^{2}x^{2}- b^{2}) = (ax + b)(ax - b), a^{2}= 1, thus a = 1 x^{2}= 9, thus x = 3 b^{2}= r^{2}, thus b = r, in this case. Therefore, (a^{2}x^{2}- b^{2}) = (3 + r)(3 - r). Thus, 9 - r^{2}= (3 + r)(3 - r). 2) 9p^{2}- 4 a^{2}= 9, thus a = 3 x^{2}= p^{2}, thus x = p b^{2}= 4, thus b = 2, in this case. Therefore, (a^{2}x^{2}- b^{2}) = (3p + 2)(3p - 2). Thus, 9p^{2}- 4 = (3p + 2)(3p - 2). Note: you can also use the decomposition method on expressions like these but you have to add the linear term into the expression with a coefficient of zero. (i.e. 4x^{2}- 9 = 4x^{2}+ 0x - 9. Now, the 0x term can be slpit into (-6x) + (6x). Performing the decompostion method on the new expression: 4x^{2}- 6x + 6x - 9, results in (2x + 3)(2x - 3).